2015
DOI: 10.1021/acs.jproteome.5b00308
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling and Functional Characterization of Multiple Post-Translational Modifications of Tubulin

Abstract: Tubulin is known to undergo unique post-translational modifications (PTMs), such as detyrosination and polyglutamylation, particularly in the unstructured carboxy-terminal tails (CTTs). However, more conventional PTMs of tubulin and their roles in the regulation of microtubule properties and functions remain poorly defined. Here, we report the comprehensive profiling of tubulin phosphorylation, acetylation, ubiquitylation, and O-GlcNAcylation in HeLa cells with a proteomic approach. Our tubulin-targeted analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…In plants tubulin acetylation has been shown for many species including A. thaliana (Tran et al, ), as well as for tubulin of different microtubular arrays (including interphase cortical MTs, preprophase band, mitotic spindle and phragmoplast) (Smertenko et al, ). This modification mainly reflects stable state of MTs (Geeraert et al, ; Giannoutsou et al, ; Liu et al, ) and is tissue‐specific and dynamically regulated during plant development (Nakagawa et al, ). Our previous data indicate that metabolic stress provokes the increase of α‐tubulin acetylation level in tobacco BY‐2 cells and is correlated with sucrose exhaustion in the cultivation medium (Lytvyn et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In plants tubulin acetylation has been shown for many species including A. thaliana (Tran et al, ), as well as for tubulin of different microtubular arrays (including interphase cortical MTs, preprophase band, mitotic spindle and phragmoplast) (Smertenko et al, ). This modification mainly reflects stable state of MTs (Geeraert et al, ; Giannoutsou et al, ; Liu et al, ) and is tissue‐specific and dynamically regulated during plant development (Nakagawa et al, ). Our previous data indicate that metabolic stress provokes the increase of α‐tubulin acetylation level in tobacco BY‐2 cells and is correlated with sucrose exhaustion in the cultivation medium (Lytvyn et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Digestion of mouse α-tubulin at AcK 40 with trypsin results in the missed cleavage at that position and thus in an unusually large tryptic peptide (6316 Da), that is not readily accessible by standard, collision-induced dissociation-based mass spectrometric sequencing. In studies using combinations of proteases, AcK 40 containing peptides were identified [34,90]. However, assignment of AcK 40 is often compromised by low identification and PTM scoring or by consideration of cleavage at AcK 40 even when unlikely, and should therefore be viewed with some caution.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, tubulin acetylation was discovered amongst many other acetylation events, and thus the novel acetylation sites of tubulin have not been verified with complementary approaches. Another study focused on tubulin and found that almost all lysine residues of aand b-tubulin can be acetylated [49], a result that might need some future verification as some of these potential modification sites are barely accessible in the folded tubulin structure, and therefore the mechanism of their acetylation is difficult to envision. Finally, one functional study showed the importance of acetylation of K252 in b-tubulin for the control of microtubule polymerization [50].…”
Section: Other Sites Of Acetylation In Tubulinmentioning
confidence: 99%